2020
DOI: 10.46586/tches.v2020.i2.73-98
|View full text |Cite
|
Sign up to set email alerts
|

FENL: an ISE to mitigate analogue micro-architectural leakage

Abstract: Ge et al. [GYH18] propose the augmented ISA (or aISA), a central tenet of which is the selective exposure of micro-architectural resources via a less opaque abstraction than normal. The aISA proposal is motivated by the need for control over such resources, for example to implement robust countermeasures against microarchitectural attacks. In this paper, we apply an aISA-style approach to challenges stemming from analogue micro-architectural leakage; examples include power-based Hamming weight and distance lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…To avoid the aforementioned leakages, the contents of the interface_d_mem_data_in_reg register should be cleared (zeroized or randomized [GMPP20]) between consecutive iterations of the loops in both functions. A simple software approach, for example, is to insert dummy store operations at the end of each iteration, sending random data to this register.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the aforementioned leakages, the contents of the interface_d_mem_data_in_reg register should be cleared (zeroized or randomized [GMPP20]) between consecutive iterations of the loops in both functions. A simple software approach, for example, is to insert dummy store operations at the end of each iteration, sending random data to this register.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was necessary to re-order instruction sequences such that given the masked representation of some x, i.e., x = (x 0 , x 1 ), a load of x 0 was not directly followed by a load of x 1 : doing so prevents accidental share combination, and thus Hamming distance leakage, in the memory interface. Where this was not possible, or not fully effective, we attempted to use fence-like instructions (see, e.g., [SSB + 19]) to load or store "dummy" random value to flush residual state; we note that a dedicated mechanism such as FENL [GMPP20] could serve the same purpose with potentially less overhead.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Gao et al [26] have demonstrated an Instruction Set Extension (ISE) to RISC-V Instruction Set Architecture (ISA). The ISE guarantees that internal states that cause leakage are cleared acting as a barrier instruction when used in sensitive programs.…”
Section: Leakage Emulators and Automatic Countermeasuresmentioning
confidence: 98%